An Engraved Gem with Centaur Found at Carthago Nova (Hispania Citerior) - Vizcaíno Sánchez, Jaime (Eikón / Imago, 2016)
We study an engraved gem from Carthago Noua. This cornelian piece shows a centaur with a branch, advancing left. This article explores the technical characteristics, date or cultural adscription of this gem, which was used as a finger ring. Specifically, we insist on the necessity to deepen the iconographical analysis of the centaurs. We think that this engraved gem shows a mythological exemplum.